Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Les cinq sexes : pourquoi mâle et femelle ne suffisent pas - Fausto-Sterling, Anne (Petite bibliothèque Payot, 2013)
Pourquoi n'y aurait-il que deux sexes, un mâle et un femelle ? Ne peut-on pas être à la fois un homme et une femme ? Voici, enfin traduit, l'essai mythique et provocateur qui offrit à la biologiste Anne Fausto-Sterling une notoriété mondiale dans le champ des études sur le genre. S'appuyant sur le cas des hermaphrodites ou "intersexes", reposant de manière radicale les questions du savoir et des violences faites au nom de la norme sociale, elle montre avec force et ironie comment il est possible de libérer les corps de l'emprise du genre
Keywords: 1900-1999; amériques; biologie; corps; cours; discipline; fem1000; premier cycle; périodes historiques; régions géographiques; sexe biologique; soc2014; thématiques; états-unis

Corps en tous genres : la dualité des sexes à l'épreuve de la science - Fausto-Sterling, Anne (Bibliotheque de l'IEC, 2012)
« Il y a deux sexes ! » Ce serait un fait de nature. La biologiste Anne Fausto-Sterling défait cette fausse évidence du sens commun, fut-il scientifique. N’y en aurait-il pas cinq, voire plus ? Ironique, cette proposition n’en est pas moins sérieuse : pour les intersexes, ni tout à fait garçons ni vraiment fille, il en va de leur vie. Va-t-on les faire entrer de force, par la chirurgie, dans l’une ou l’autre catégorie ? Et, quand ils envoient des messages différents, qui, des chromosomes, des hormones, du cerveau ou du squelette, a le dernier mot ? L’enjeu, ce sont les exceptions mais aussi la règle, à savoir tout le monde ! Le partage entre deux sexes est toujours une opération sociale. C’est bien la société qui tranche dans les variations attestées pour donner un sexe au corps. Et, quand le médecin ou le savant parlent de sexe, ou de sexualité, c’est encore la société que l’on entend. Loin d’être neutre, la science est donc toujours située : telle est l’une des leçons de cet ouvrage, devenu un classique depuis sa publication aux Etats-Unis en 2000. La critique du biologisme par une scientifique du sérail trouble nos oppositions convenues –entre genre (social) et sexe (biologique), entre culture et nature. Ainsi ne pourra-t-on plus dire qu’il faut choisir entre féminisme et science. Gai savoir que celui offert par ce livre illustré avec humour et érudition : la biologie, c’est bien la politique continuée par d’autres moyens.
Keywords: 1900-1999; LGBTQIA2+; amériques; biologie; cours; cycles supérieurs; discipline; fem1000; fem7000; identités LGBTQIA2+; lit3220; premier cycle; psy4910; périodes historiques; régions géographiques; sciences humaines; sciences sociales; sexes; thématiques; états-unis

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"--Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Minorités sexuelles, Internet et santé - Lévy, Joseph J. (Presses de l'Université du Québec, 2011)
Les nouvelles technologies de communication, et notamment Internet, ont transformé à la fois les stratégies relationnelles et la transmission et le partage des informations dans toutes les sphères de la vie, incluant le domaine de la santé. Pour les minorités sexuelles qui sont confrontées à de multiples formes de discrimination et de marginalisation, Internet est devenu un puissant moyen de s’organiser, d’informer et d’intervenir dans le champ de la santé. Les associations et organismes communautaires ciblant ces populations proposent aujourd’hui un ensemble de sites et de stratégies de soutien et d’intervention. Ces outils synchrones et asynchrones disponibles en ligne visent l’amélioration de la santé mentale et physique, des relations interpersonnelles et la prévention des ITSS et du VIH/sida. Par contre, les usages qui varient en fonction des populations LGBT peuvent aussi concourir à la prise de risques et à des formes de dépendance. Afin de mieux comprendre les enjeux entourant les usages d’Internet et la santé, cet ouvrage, réalisé grâce à l’appui de l’équipe pancanadienne Sexualités et genres ;: vulnérabilité et résilience (SVR), regroupe les contributions de chercheurs de l’équipe qui ont effectué des travaux sur Internet et la santé ainsi que d’intervenants impliqués dans des organismes communautaires, qui utilisent des sites Internet à des fins de réseautage, de transfert d’informations et d’interventions en ligne dans les contextes québécois et canadien.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; internet; militance; médecine; organisme communautaire; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; réseaux sociaux; santé; sciences de la santé; sciences humaines; sexualité; soc2014; système médical; systèmes d'oppressions; thématiques; travail social

Queer Diagnoses: Parallels and Contrasts in the History of Homosexuality, Gender Variance, and the Diagnostic and Statistical Manual - Drescher, Jack (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
The American Psychiatric Association (APA) is in the process of revising its Diagnostic and Statistical Manual (DSM), with the DSM-V having an anticipated publication date of 2012. As part of that ongoing process, in May 2008, APA announced its appointment of the Work Group on Sexual and Gender Identity Disorders (WGSGID). The announcement generated a flurry of concerned and anxious responses in the lesbian, gay, bisexual, and transgender (LGBT) community, mostly focused on the status of the diagnostic categories of Gender Identity Disorder (GID) (for both children and adolescents and adults). Activists argued, as in the case of homosexuality in the 1970s, that it is wrong to label expressions of gender variance as symptoms of a mental disorder and that perpetuating DSM-IV-TR’s GID diagnoses in the DSM-V would further stigmatize and cause harm to transgender individuals. Other advocates in the trans community expressed concern that deleting GID would lead to denying medical and surgical care for transgender adults. This review explores how criticisms of the existing GID diagnoses parallel and contrast with earlier historical events that led APA to remove homosexuality from the DSM in 1973. It begins with a brief introduction to binary formulations that lead not only to linkages of sexual orientation and gender identity, but also to scientific and clinical etiological theories that implicitly moralize about matters of sexuality and gender. Next is a review of the history of how homosexuality came to be removed from the DSM-II in 1973 and how, not long thereafter, the GID diagnoses found their way into DSM-III in 1980. Similarities and differences in the relationships of homosexuality and gender identity to psychiatric and medical thinking are elucidated. Following a discussion of these issues, the author recommends changes in the DSM-V and some internal and public actions that the American Psychiatric Association should take.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; inégalités; premier cycle; psychiatrie; régions géographiques; santé; sciences; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; transidentité; violences; états-unis

L’impact des violences structurelle et conjugale en contexte migratoire: Perceptions d’intervenants pour le contrer - Rojas-Viger, Celia (Nouvelles pratiques sociales, 2008)
Résumé Le Canada et le Québec, sociétés pluriethniques, possèdent des politiques et des programmes de promotion et de prévention pour contrer les violences faites aux femmes, mais reconnaissent que le défi est de taille dans le contexte migratoire. Les immigrantes, confrontées à la violence conjugale, ne disposent souvent pas d’accessibilité culturelle aux services sociaux et de santé ou n’obtiennent pas de réponse adéquate à leurs besoins. Toutefois, certains organismes ont des projets pour leur venir en aide mais ils ne sont pas systématiques. L’article présente les résultats d’une recherche exploratoire, avec approche ethnologique, qui documente la perception de 10 intervenants d’organismes communautaires et institutionnels concernant leurs activités dans le domaine et leur préoccupation pour la promotion et la prévention primaire, même si leurs pratiques concrètes sont surtout centrées sur la prévention secondaire. Maints empêchements les limitent, mais leurs perceptions des réponses promotionnelles et préventives mettent en lumière l’impact de la violence structurelle et de la violence conjugale et orientent les perspectives de renouvellement des pratiques d’intervention sociosanitaire en matière de violence conjugale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; médecine; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; systèmes d'oppressions; thématiques; trs3500; violence systémique; violences; violences conjugales

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

The daughter's seduction: Feminism and psychoanalysis - Gallop, Jane (Cornell University Press, 1982)
At the time this book was published in 1982, Jane Gallop was professor of French at Miami University; she has also written Intersections: A Reading of Sade with Bataille, Blanchot, and Klossowski. She wrote in the Introduction, "[the book] studies the relation between contemporary feminist theory and the psychoanalysis of Jacques Lacan... it enters into a network of problems: problems of sexual difference, of desire, of reading, or writing, of power, of family, of phallocentrism and of language... this book is ... a contribution to the sort of thinking it describes---that is, a contribution to French psychoanalytic feminist thought from the vantage point of these English-speaking shores." (p.11) She adds, "The book begins by calling into question certain feminist assumptions through the agency of Lacanian psychoanalysis. It ends by calling into question certain psychoanalytic positions through the agency of feminist writing." (p.15) She states that "[Freudian] Phallocentrism seems wrong to [Ernest] Jones: that is, immoral by virtue of being 'excessive, immoderate,' which is to say, unreconcilable with a 'sense of proportion.' The phallic disproportion brings him... to champion the claims of an 'underestimated' female sexuality to a more balanced, more proportionate estimate. His 'sense of proportion,' his spirit of fair play, will be sufficiently scandalized to provoke his only major departure from Freud's theory." (p. 16) She observes that in an article, "[Stephen] Heath begins by informing us that ... Lacan's 1972/73 seminar [is] devoted to 'what Freud expressly left aside... What does woman want?' ... Yet Lacan said nothing of devotion... Lacan speaks of a beginning... of a relation to this question: far from devoting himself to women he is simply at the stage of approach, first and rather aggressive encounter." (p. 43) This book will be of interest to feminists studying psychoanalysis, or to students of Lacan.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; thématiques; écriture des femmes*; états-unis

Visual Pleasure and Narrative Cinema - Mulvey, Laura (Screen, 1975)
Cet article se propose d'utiliser la psychanalyse pour découvrir où et comment la fascination du film est renforcée par des schémas de fascination préexistants déjà à l'œuvre au sein du sujet individuel et des formations sociales qui l'ont façonné. Il prend pour point de départ la façon dont le cinéma reflète, révèle et même joue sur la lecture droite et socialement établie de la différence sexuelle qui commande les images, les regards érotiques et le spectacle. Il est utile de comprendre ce qu'a été le cinéma, comment sa magie a opéré dans le passé, tout en tentant une théorie et une pratique qui remettront en cause ce cinéma du passé. La théorie psychanalytique est ainsi appropriée ici comme une arme politique, démontrant la manière dont l'inconscient de la société patriarcale a structuré la forme cinématographique.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cinéma; cours; discipline; fem1000; fem3200; male gaze; premier cycle; privilèges; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences; sciences humaines; sofia; systèmes d'oppressions; états-unis

Peau noire, masques blancs - Fanon, Frantz (Seuil, 1971)
La décolonisation faite, cet essai de compréhension du rapport Noir-Blanc a gardé toute sa valeur prophétique : car le racisme, malgré les horreurs dont il a affligé le monde, reste un problème d'avenir. Il est ici abordé et combattu de front, avec toutes les ressources des sciences de l'homme et avec la passion de celui qui allait devenir un maître à penser pour beaucoup d'intellectuels du tiers monde.
Keywords: 1900-1999; 1950-1959; amériques; antilles; approches et analyses; colonialisme; cours; discipline; décolonialisme; europe; fem1000; femmes* noires; france; féminisme décolonial; har4600; histoire; postcolonialisme; premier cycle; psychanalyse; périodes historiques; racisme; régions géographiques; sciences; sciences humaines; systèmes d'oppressions